PENDIDIKAN SENI BERBASIS KOMUNITAS SEBAGAI SARANA PEMBERDAYAAN SOSIAL DI INDONESIA - Moh Kevin Sulistyo Adjie; Hartono; Restu Lanjari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the role of community-based art education as a means of social empowerment in Indonesia, emphasizing its collaborative, participatory, and sustainable dimensions. Using a descriptive qualitative method with a multiple case study design, the research was conducted in three art communities: Komunitas Mural Warna Kota in Yogyakarta, Seni untuk Semua in Surabaya, and Kampung Kreatif in Bandung. Data were collected over eight months through participatory observation, in-depth interviews, and document analysis. The findings reveal that community art education serves a dual function—both as a medium of aesthetic expression and as a social practice that fosters critical awareness, solidarity, and community self-reliance. Collaboration among artists, non-governmental organizations (NGOs), and local governments proved effective in ensuring program sustainability through the implementation of gotong royong (mutual cooperation) values and the strengthening of local identity. This study asserts that community-based art education represents a form of humanistic pedagogy that balances aesthetic intelligence with social responsibility and contributes to the development of art education theory as a form of social praxis relevant to the Indonesian cultural context.